2011
DOI: 10.1159/000320333
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Related Factors of Urinary Incontinence among Hebei Women of China

Abstract: Background/Aims: The aim of this study was to assess the prevalence and related factors of different types of urinary incontinence (UI) among Hebei women in China. Methods: A total of 2,500 women aged 20 years or more were sampled and interviewed face-to-face by well-trained interviewers. Results: Among these women, 35.2% (862/2,448) had UI. The prevalence of stress, urge, and mixed UI was 26.4% (647/2,448), 1.9% (47/2,448), and 6.9% (168/2,448), respectively. In multivariable logistic regression, age, constip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
6
21
2
Order By: Relevance
“…Of these, 151 articles were excluded because they did not meet the inclusion criteria, for example prevalence studies in pregnant women. Finally, a total of 54 studies were included in the systematic review 2,6,8,9,23,26‐71 . All studies underwent methodological quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 151 articles were excluded because they did not meet the inclusion criteria, for example prevalence studies in pregnant women. Finally, a total of 54 studies were included in the systematic review 2,6,8,9,23,26‐71 . All studies underwent methodological quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Funnel plot analysis of 54 studies. Only one study on the left side (*) below is totally out of distribution 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Danforth et al () in his study identified that BMI, type 2 diabetes mellitus, parity, hysterectomy and cigarette smoking were strongly associated with UI. In addition Wu et al () identified age, BMI, constipation, pelvic organ prolapse, dysmenorrhoea, vaginitis and cervicitis, dystocia, foetal weight, number of abortions and caesarean section and were the major risk factors for the type of UI.…”
Section: Resultsmentioning
confidence: 99%
“…Early or late menarcheal age has great influence on the health of women. Researchers have found that an early menarcheal age was associated with an increased risk for endometriosis, obesity and type 2 diabetes [1,2,3], as well as several hormone-associated cancers, such as breast cancer, myomatosis, multiple sclerosis, endometrial cancer and uterine leiomyomata [4,5,6,7,8,9], and late menarcheal age was associated with urinary incontinence, senile dementia and osteoporosis [10,11]. …”
Section: Introductionmentioning
confidence: 99%